Yellow Fever Virus NS3 Plays an Essential Role in Virus Assembly Independent of Its Known Enzymatic Functions - Patkar, Chinmay G. (American Society for Microbiology (ASM), 2008)
In flaviviruses it has been proposed that there is a coupling between genome replication and virion assembly and that nonstructural proteins are involved in this process. It was previously reported that mutations in yellow fever virus (YFV) nonstructural protein NS2A blocked production of infectious virus and that this block could be released by a suppressor mutation in NS3. Here, based on studies using a YFV replicon-based trans-packaging system as well as full-length YFV cDNA, we report that mutation of a conserved tryptophan at position 349 in the helicase domain of NS3 blocks production of infectious virus particles, revealing an as-yet-unknown role for NS3 in virus assembly. Mutation of tryptophan 349 to alanine (W349A) had no effect on viral replication, as demonstrated by wild-type levels of viral RNA amplification and protein expression in W349A-transfected cells. Although release of infectious virus was not detected, release of capsidless subviral particles was not blocked. The assembly defect in W349A could be trans-complemented inefficiently using BHK-REP cells (a cell line containing persistently replicating YFV replicon RNA). trans-complementation was also demonstrated by supplying wild-type NS2B-3 or NS3 protein alone as well as by supplying inactive NS2B-3 protein, indicating that this function of NS3 in virus assembly was independent of its known enzymatic functions.